Predictors of clinical response to erenumab in patients with migraine - Olga Lekontseva; Meng Wang; Farnaz Amoozegar (SAGE Publishing, 2022)
Background: Anti-CGRP monoclonal antibodies have emerged as efficacious preventive therapies for some, but not all patients with migraine. It is not yet fully understood what predicts treatment response. Objective: To identify factors associated with good or poor response to erenumab, the first available CGRP monoclonal antibody. Methods: A chart review of patients with migraine from a large headache center who received at least three 4-weekly doses of erenumab between 2018 and 2020 was conducted. Clinical variables were compared between erenumab responders (defined as ≥30% reduction in monthly headache or migraine days at 3 months) and non-responders via logistic regression analyses. Results: Among 90 enrolled patients, 62.2% were erenumab responders and 37.8% non-responders. A significantly larger proportion of non-responders were unemployed (58.8% vs. 28.6%), had complex diagnosis (chronic migraine overlapping another primary or secondary headache) (47.1% vs. 14.3%), higher monthly headache days (30 vs. 25.5) and migraine days (20 vs. 12), a higher frequency of daily headache (76.5% vs. 48.2%), and failed more preventive therapies (5.5 vs. 3). Based on logistic regressions, erenumab responsiveness did not significantly associate with duration of migraine, presence of aura, medication overuse, number of concurrent preventives, response to onabotulinumtoxinA or triptans, or certain comorbidities and substance use. Conclusions: This work may help improve selection of patients who may benefit from erenumab, but further prospective research studies are needed.